Hemodynamic and Lesion Characteristics Associated with Discordance between the Instantaneous Wave-Free Ratio and Fractional Flow Reserve. (14th July 2019) - Arashi, Hiroyuki; Satomi, Natsuko; Ishida, Issei; Soontorndhada, Kanintorn; Ebihara, Suguru; Tanaka, Kazuki; Otsuki, Hisao; Nakao, Masashi; Jujo, Kentaro; Yamaguchi, Junichi; Hagiwara, Nobuhisa
Abstract : Background . The instantaneous wave-free ratio (iFR) is an invasive coronary physiological index that is not inferior to fractional flow reserve- (FFR-) guided revascularization. The indexes of iFR and FFR are similar and closely correlated, but there are a few key differences. Previous studies suggested that patient characteristics and lesion severity could induce discordance between iFR and FFR. This study aimed to clarify the hemodynamics and lesion characteristics that influence discordance between iFR and FFR. Methods . In this retrospective study, we enrolled 225 patients (304 lesions) who underwent clinically indicated invasive coronary angiography and both iFR and FFR examinations between 2012 and 2017. We included only patients who underwent right heart catheterization and had blood pressure and heart rates recorded immediately prior to iFR and FFR. Results . Discordance (iFR ≤0.89 and FFR >0.8 or iFR >0.89 and FFR ≤0.8) was observed in 80 lesions (26.3%). The heart rate, rate-pressure product, and cardiac index tended to be higher in the iFR ≤0.89 group than in the iFR >0.89 group. These trends were not seen between the FFR ≤0.8 group and FFR >0.8 group. A multivariate analysis showed that independent predictors of iFR ≤0.89 and FFR >0.8 discordance were female sex and higher rate-pressure product. iFR >0.89 and FFR ≤0.8 discordance was rare in hemodialysis patients. Conclusion . Even if iFR is functionally significant in intermediate stenosis, additional FFR evaluations should be considered for women, especially those with a high rate-pressure product, to avoid unnecessary percutaneous coronary intervention. If iFR is not functionally significant with intermediate stenosis in hemodialysis patients, then further FFR evaluations are unnecessary.